Epidemiology, literacy, risk factors, and clinical status of oral cancer in East Africa: A scoping review - Aminu, Kafayat; Aladelusi, Timothy Olukunle; Adisa, Akinyele Olumuyiwa; Ezeagu, Chiamaka Norah; Salami, Afeez Abolarinwa; Nwafor, Jacob Njideka; Uwambaye, Peace; Amzat, Jimoh; Murererehe, Julienne; Omoleke, Semeeh Akinwale; Abdulaziz, Mohammed; Jayasinghe, Ruwan Duminda; et al. (PloS one, 2025)
Oral cancer (OC) is a topical public health issue in East Africa due to increasing incidence of the disease. Public health efforts to address the oral cancer burden depends largely on the available empirical evidence. Hence, this scoping review aims to map the existing empirical evidence on oral cancer in East African countries. The Preferred Reporting Items for Systematic Review and Meta-analysis Extension for Scoping Reviews (PRISMA-ScR) was used as a guideline for reporting this scoping review. Additionally, we ensured quality assessment of the methodology and reporting process of this study using the AMSTAR 2 checklist. We conducted a systematic search of nine research databases on 17th November 2023, and reviewed studies published in English from year 2000 to 17th November 2023. The team developed data extraction form and data extraction was done by two reviewers. Thematic analyses were conducted manually and presented in texts, tables and flow chart. Only 30 full manuscripts were included in this review. Twenty-nine out of 30 studies were either hospital- or clinic-based while two were community-based. Only four studies showed gaps and obvious disparities in awareness and knowledge levels across East Africa, however, higher levels of awareness were reported among dentists and dental patients relative to the general population. Most neoplasms were presented and diagnosed late. The review finding also highlighted the significant impact of Toombak use on the oral microbiome composition, potentially contributing to oral cancer risks. Further, this review elucidated the prognostic relevance of PD-L1 expression at the invasive tumor front and microbial composition, with Candida correlating with adverse prognosis and Malassezia showing associations with improved survival rates. Also, Toombak usage, tumor staging, and mucosal field alterations emerged as predictors of local recurrence, while lymph node involvement and extranodal extension were associated with regional recurrence among Sudanese cohorts. Finally, a few studies undertook an evaluation of instrument validity for OC detection, revealing promising outcomes concerning diagnostic accuracy and instrument reliability. There is a dire need for targeted interventions and early detection strategies tailored to the unique epidemiological and clinical profiles of oral and maxillofacial tumors in East Africa. Public health interventions aimed at curbing the prevalence of Toombak use and promoting healthier lifestyle choices to reduce the oral diseases incidence in Sudan and other regions where these behaviors are prevalent remain germane.